Associations between obesity, self-reported weakness and their combinations with mortality in nursing home residents - TUFAN ÇİNÇİN, ASLI (My University, 2023)
Objectives There are studies on associations between obesity and mortality in nursing home (NH) residents, but the presence of concomitant muscle weakness has not been examined. We considered that self-reported weakness might be a low muscle strength proxy marker. We aimed to examine associations of obesity alone, self-reported muscle weakness alone, and their combination with mortality in NH residents. Methods This is a retrospective longitudinal follow-up study. We noted age, sex, nutritional status, functionality, number of chronic diseases, and regular medication. Obesity was assessed by the body fat-percentage method estimated by bioimpedance analysis. Weakness was identified by self-reported muscle weakness. Survival was evaluated with a univariate log-rank test and multivariate Cox regression analyses. Results We included 214 participants. In a median follow-up time of 46 months, mortality occurred in 37.4%. In multivariate analysis adjusted by age, sex, undernutrition, number of chronic diseases, and regular medication, functional scores; \"non-weak non-obese\" participants or \"weak alone\" participants or \"weak+obese\" participants had higher mortality risk when compared with the \"obesity alone\" participants [hazard ratio (HR) = 2.6, 95% confidence interval (CI) = 1.2-5.5, p = 0.01; HR = 2.6, 95% CI = 1.2-5.9, p = 0.02; HR = 3.0, 95% CI = 1.2-7.7, p = 0.02]. Conclusion This is the first report showing that obesity was associated with lower mortality risk if the weakness was not present in NH residents. However, obesity with concomitant weakness was associated with mortality risk similar to non-weak non-obese or weak alone participants. Our study suggests a simple consideration of weakness that can easily be integrated into everyday practice.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Mortality; Nursing home; obesity; self-reported; muscle weakness; BODY-MASS INDEX; ALL-CAUSE MORTALITY; SARCOPENIC OBESITY; OLDER-PEOPLE; RATED HEALTH; WEIGHT-LOSS; DEMENTIA; PARADOX; METAANALYSIS; SURVIVAL; Mortality; Nursing home; obesity; self-reported; muscle weakness